A better choice : healthcare solutions for America - Goodman, John C. (The Independent Institute, 2015)
Despite having surmounted numerous obstacles, the Affordable Care Act-also commonly known as "Obamacare"--Remains highly controversial and faces ongoing legal and political challenges. The law's staunchest critics want to repeal and replace the entire law, while even its supporters acknowledge that serious changes are needed. The question is: replace it with what? In A Better Choice: Healthcare Solutions for America, economist and John C. Goodman answers the question clearly and concisely. For anyone who wants to better understand Obamacare's most serious problems and learn about some of the bo